1-calcium phosphate-uracil inhibits intraperitoneal metastasis by suppressing FAK in epithelial ovarian cancer. Issue 16 (18th August 2019) - Peng, Jing; Yang, Xiaoqian; Li, Xiaofeng; Gao, Hao; Liu, Na; Guo, Xiaoqing
ABSTRACT: The high mortality of epithelial ovarian cancer (EOC) is primarily due to vast intraperitoneal dissemination. 1-calcium phosphate-uracil (1-CP-U) has previously shown the function of inhibiting migration and invasion in multiple tumor cell lines. In this study, we further assessed the possible role of 1-CP-U in suppressing the peritoneal metastasis of EOC cells. First, we demonstrated that 1-CP-U had an inhibitory effect on EOC cells in cell-matrix adhesion, migration and invasion assay in vitro . Within the in vivo model, animals were intraperitoneally inoculated with SKOV3-Luc cells and then 1-CP-U intraperitoneal ( i.p .) injection was performed every 5 d for a total of 3 wk. At the 7th d, omenta from each group were analyzed with luciferase activity and bioluminescence imaging assay, which showed a significant reduction of luciferase activity in the omenta from 1-CP-U group. In addition, the rest mice continued treatment and consistent detection of bioluminescence imaging. The data indicated that intraperitoneal metastatic nodules were less-developed in 1-CP-U group. Peritoneal metastatic tumor nodules were detected for immunofluorescent staining, which showed a reduction in FAK and p-FAK staining with 1-CP-U treatment group. Meanwhile, expressions of FAK and its downstream signaling were detected by western blot in tumor tissues and EOC cell lines, which showed significant decreases in the 1-CP-U treatment group. In conclusion, 1-CP-U had a profound inhibitory effect on adhesion, invasion and metastasis of EOC in vitro and suppressed intraperitoneal dissemination and cancer growth in vivo assay, which was associated with inhibition on the FAK pathway.